Kinetics and Mechanism of Hydrolysis of Synthesized 4-Bromo Anilline Phosphoro Mono-Amidate via Conjugate Acid Species (Barium Salt) - R.K. Chourasia, Nimisha; Bhadoria, A.K.S.; Shivhare, R.L. (Asian Journal of Chemistry, 2010)
The study of kinetics of hydrolysis of 4-bromo aniline phsophoro mono-amidate, which is a substituted ester of orthopbosphoric acid has been carried out in acid concentration ranging from 1.0-6.0 M of HCl at 70°C. The solvent used is 10% aqueous (v/v) dioxanes water mixture. The maximum rate of hydrolysis was observed at 4.0 M HCI; later at higher acid region the rates decreased due to water activity. The various concepts such as Hammett acidity-function, Zucker-Hammett hypothesis, Bunnett parameter, are an evidence to predict biomolecularity of the reaction. The Arrhenius parameters, i.e., energy of activation, frequency factor and entropy of activation are falling in the range of bimolecularity of the reaction. The effects of ionic strength were used to determine probable reaction path.